Initial investigations into characterizing DIY E-textile stretch sensors - Stewart, R.; Skach, S. (Proceedings of the 4th International Conference on Movement Computing, 2017)
This paper evaluates three electronic textile (e-textile) stretch sensors commonly constructed for bespoke applications: two variations of fabric knit with a stainless steel and polyester yarn, and knit fabric coated with a conductive polymer. Two versions of the knit stainless steel and polyester yarn sensor, one hand and one machine knit, are evaluated. All of the materials used in the construction of the sensors are accessible to designers and engineers, and are commonly used in wearable technology projects, particularly for arts performance. However, the properties of each sensor have not before been formally analysed. We evaluate the sensors' performance when being stretched and released.